Clustering Data Kejadian Tsunami Yang Disebabkan Oleh Gempa Bumi Dengan Menggunakan Algoritma K-Medoids - Daniel Alex Saroha Simamora; Muhammad Tanzil Furqon; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Tsunami is a natural events caused by sudden alteration in sea surface vertically, causing displacement of a large volume of water. Underwater volcano eruption, earthquake that is centered under the sea, and submarine landslide are some of the causes of sudden sea level change. Tsunami have occurred many times and causing many damages and fatalities. Tsunami often occurred so suddenly and cannot be predicted is the main reason for so many damages and fatalities, and the lack of knowledge and awareness are also worsen the effect of tsunami. K-Medoids is one of many clustering method which is applied to the dataset which have outlier. Subject in this research is a clustering application using K-Medoids to cluster the tsunami event which caused by earthquake dataset. Dataset used in this research come from the tsunami events database from the official site of National Oceanic and Atmospheric Administration (NOAA). The outcome from this research is a system that able to do clustering process on the tsunami events dataset using K-Medoids method. From the test, it is showed that the best number of clusters for tsunami events dataset is 2 clusters.